A comparative study of triacylglycerol composition in Chinese human milk within different lactation stages and imported infant formula by SFC coupled with Q-TOF-MS. (15th April 2017) - Tu, Anqi; Ma, Qiang; Bai, Hua; Du, Zhenxia
Highlights: A high efficient method for determining TAGs in milk samples was established. Over 60 TAGs in human milk and 50 TAG in infant formula were identified. Results showed differences between Chinese human milk and imported infant formula. Principal component analysis (PCA) was applied for data processing. Abstract: Triacylglycerols (TAGs) as the major component of milk fat are significant factors to ensure the healthy growth of infants. An efficient method for identifying TAGs in human milk (HM) and infant formula (IF) was established using supercritical fluid chromatograph (SFC) coupled with quadruple time-of-flight mass spectrometry (Q-TOF-MS). The results indicated the feasibility of this method with satisfactory recoveries (>80%) and correlation coefficients ( r 2  ⩾ 0.993). More than 60 TAGs in HM and 50 TAGs in IF were identified. The profiling results demonstrated that TAGs in HM were greatly affected by lactation stage. Significant differences were found between HM and IF, such as much higher medium chain TAGs and saturated TAGs in IF, indicating that the formulas developed by foreign manufacturers were not suitable for Chinese babies. This high-throughput method exhibits a huge potential for analysis of milk samples and the result may serve as an important guide for Chinese infants diet.